Can myocardial performance index predict early cardiac risks in erectile dysfunction?. (9th April 2021) - Ardahanlı, İsa; Celik, Mehmet
Abstract: Aim: Myocardial performance index (MPI) is an easy-to-apply and non-invasive method that shows both systolic and diastolic functions of the heart. In this study, it was aimed to evaluate the relationship between erectile dysfunction (ED) and MPI. Methods: The study included 45 male patients admitted to the urology outpatient clinic for ED and 48 healthy male volunteers. Echocardiographic evaluation of all participants was performed. Isovolumetric contraction time (IVCT), isovolumetric relaxation time (IVRT) and ejection time (ET) were measured. MPI was calculated using the IVCT + IVRT/ET formula. Results: The average age of the study population was 50 ± 5.3. Early diastolic mitral inflow (E)/late diastolic mitral inflow (A) ratio was significantly lower in the ED group ( p  ≤ 0.05). In the TDI evaluation between the groups, while early diastolic mitral annular velocity (Em) was significantly higher in the ED group, there was no significant difference in late diastolic mitral annular velocity (Am) and systolic peak velocities (Sm) ( p  < 0.01 and p  = 0.417 and p  = 0.092, respectively). While IVRT was significantly lower in the ED group ( p  < 0.05), there was no significant difference in IVCT and ET ( p  = 311 and p  = 0.261, respectively). MPI was statistically significantly higher in the ED group ( p  < 0.05). Conclusion: ED has been found to affect MPI. This parameter, which is easily and non-invasively measured, can be used to predict the risk of CVDs in ED.